The Effect Of Media Use Behavior On The Preference For Smartphone Specifications - Hwang, Dukyun; Park, Sangin (European Scientific Journal, ESJ, 2016)
The paper aims to analyze the effect of media use behavior of cellphone users on the preferences for cellphone specifications. Based on the survey data of the Korean Information Society Development Institute and data on hardware attributes of mobile phone models, we employed a mixed logit model for the estimation of the interactions between consumer attributes and product characteristics. Since cellphone producers are sensitive to cellphone customers’ preferences for hardware specifications, this study’s results can provide a clue to predict technological changes on cellphone hardware.